Formulation and evaluation of mixed matrix gastroretentive drug delivery for famotidine - Patel, Dasharath M; Patel, Mehul J; Patel, Ankit N; Patel, Chhagan N (International Journal of Pharmaceutical Investigation)
Introduction: Present investigation describes an influence of ratio of Gelucire 43/01(hydrophobic) to hydroxypropyl methylcellulose K4M (HPMC K4M) (hydrophilic) and different fillers on release of famotidine from gastro-retentive tablets using 32 full factorial design. Ratio of Gelucire 43/01 to HPMC K4M (X1) and the type of filler (X2) were selected as independent variables while buoyancy lag time (BLT), drug release at 1h (Q1), 6h (Q6), and the 12h (Q12) were selected as dependent variables. Materials and Methods: Gastro-retentive tablets of famotidine were prepared by a solvent free melt granulation technique using Gelucire 43/01 as a hydrophobic meltable binder. HPMC K4M and sodium bicarbonate were used as matrixing agent and gas-generating agent, respectively. Prepared tablets were evaluated for in vitro dissolution, in vitro buoyancy, friability, hardness, drug content and weight variation. Dissolution data were fitted to various models to ascertain kinetics of drug release. The data were analyzed using regression analysis and analysis of variance. Results: All formulations (F1-F9) showed floating within 3min and had total floating time of more than 12h. It was observed that a type of filler and the ratio of Gelucire 43/01 to HPMC K4M had significant influence on buoyancy lag time (P = 0.037) and Q6 (P = 0.011), respectively without significant influence on Q1 and Q12. Conclusion: Formulation F5 was selected as an optimum formulation as it showed more similarity in dissolution profile with theoretical profile (Similarity factor, f2 = 83.01). The dissolution of batch F5 can be described by zero order kinetics (r2 = 0.9914) with anomalous (non-Fickian) diffusion as a release mechanism (n = 0.559). The difference observed in in vitro release profile after temperature sensitivity study at 40°C for 1 month was insignificant.
Keywords: Buoyancy lag time; full factorial design; Gelucire 43/01; melt granulation